La cultura como mecanismo de gobierno y control en las organizaciones cooperativas - Hernández Ortiz, Mª Jesús; Ruiz Jiménez, Carmen; García Martí, Elia (REVESCO. Revista de Estudios Cooperativos, 2008)
In this paper we try to define the culture as a Basic piece in the organizational behaviour in a cooperative. This culture includes a group of social norms, values, principles and common behaviors of people which define the organization. The objective of this paper is to study the role of the culture in the cooperative, as a people project who try to create social wealth in a democratic group of people. We try to explain questions such as the culture as a different element of these organizations, the existence of different and specific cultural characteristic and the function of this culture in the cooperative government.